Enhancing Women's Capacity in Funeral Management: A Community Service Study in Lima Puluh Kota Regency - Salma, Zakiati; Ardhi, Aisha Satira (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This community service aims to enhance the capacity of women in managing funeral rites in Lima Puluh Kota Regency, West Sumatra. Through a series of training sessions conducted in six locations, this program is designed to empower women to be more confident and skilled in performing funeral management tasks according to Islamic law. The methods include lectures, demonstrations, and hands-on practice, enabling participants to understand and practically apply the necessary skills. The results of the community service show a significant improvement in the participants' technical skills and confidence, as well as a positive change in women's active participation in religious activities within the community. Additionally, this training successfully shifted societal perceptions of women's roles, recognizing them as capable and important in funeral management. In conclusion, this program not only contributes to women's empowerment but also to the development of a more inclusive and empowered community. The program has the potential to be replicated in other regions with similar cultural contexts, thereby broadening its impact on women's empowerment and community capacity building.